2019
DOI: 10.1097/md.0000000000017539
|View full text |Cite
|
Sign up to set email alerts
|

Does relatively low iodine intake contribute to thyroid cancer? An ecological comparison of epidemiology

Abstract: Research on the relationship between iodine intake and thyroid cancer (TC) risk is limited, and the findings are inconclusive. The objective of this study was to provide emerging evidence for the association between iodine intake and TC risk in a Chinese population.An ecological study of epidemiology is used to compare the iodine intake among populations with different TC incidence in Zhoushan, China. Incidence rates of TC were investigated and compared among four counties of the Zhoushan Islands from 2014 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
(27 reference statements)
0
6
0
1
Order By: Relevance
“…Furthermore, Santos et al (14) used reservoir water iodine content combined with UIC to evaluate chronic iodine exposure in thyroid histology pattern research. Zhang et al (15) investigated iodized salt consumption combined with UIC to estimate long-term iodine intake. However, this ecology-based integrated assessment design of iodine exposure (which utilized water iodine or iodized salt consumption combined with the UIC) is rarely applied for the analysis of clinicopathological characteristics in PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Santos et al (14) used reservoir water iodine content combined with UIC to evaluate chronic iodine exposure in thyroid histology pattern research. Zhang et al (15) investigated iodized salt consumption combined with UIC to estimate long-term iodine intake. However, this ecology-based integrated assessment design of iodine exposure (which utilized water iodine or iodized salt consumption combined with the UIC) is rarely applied for the analysis of clinicopathological characteristics in PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Cardis's study showed that the risk of radiation-related thyroid cancer was 3-fold higher in iodine-deficient areas than elsewhere and that administration of potassium iodide as a dietary supplement reduced the risk of radiation-related thyroid cancer (25) . A study in Zhoushan, China, also showed that the population with a high thyroid cancer incidence had a lower iodised salt consumption and a lower UIC than populations with a relatively low thyroid cancer incidence (26) . Similarly, in our study, it is also found that Daishan County, which is located in Zhoushan, had a low CRQIS (20-70 %) in recent years (27,28) and had a high incidence of thyroid cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Es importante establecer que factores de riesgo explican la alta y creciente incidencia de CT en nuestro país. En los últimos años se han asociado con mayor riesgo de CT, además de la exposición a radiación, la obesidad, el sedentarismo y la diabetes mellitus 2 [19][20][21] , contaminantes químicos como bisfenol A y cadmio 21,22 , la baja ingesta de yodo y la ingesta excesiva de nitritos 24,25 y factores reproductivos en la mujer 26 .…”
Section: Discussionunclassified